THU0508 Improvement in Treat To Target Serum Urate Levels: Results from A Comparison between The Gema and The Gema-II Audits. (15th July 2016) - Perez-Ruiz, F.; Andres, M.; Diaz-Torne, C.; de Miguel, E.; Moragues, C.; Sivera, F.; Jimenez-Palop, M.; Sanchez-Piedra, C.
Abstract : Background: The prior GEMA (1) audit included patients before the EULAR 2006 recommendations were published (2), showing poor adherence to the EULAR recomendations in both crystal-based diagnosis and target urate levels. Objectives: 1) assess the current quality of care in gout patients in Spain and 2) compare the current management with previous audit data. Methods: The GEMA-II study included patients from EULAR 2006 to ACR 2012 guidelines. Agreement on diagnosis and treatment of gout with the EULAR 2006 recommendations was assessed. The selection of patient's files for review was performed selecting a stratified 2-stage sampling of centers according to national population statistics. A random sample in each unit with a diagnosis code of gout (ICD, R9) was centrally selected. The sample size was estimated according to previous results and expected outcomes. The main co-principal variables were >50% improvement in the rate of gold-standard diagnosis and >50% improvement in the rate of patients at target serum urate levels. Results: Data from 511 randomly selected clinical records from 38 units were included. Out of the 38 units, 93% reported having a polarized microscopy facility at the office. sUA at final visit was available in 479/511 (93.7%). Samples from the two audits (GEMA and GEMA-II) did not differ in age, sex distribution or time from onset to first visit. Crystal-based diagnosis was performed in 209/803 (26.0%) and 162/511 (31.7%) in the GEMA and GEMA-II studies (p=0, 030, 5.7% improvement, not reaching endpoint >50%). By contrast, the pre-defined improvement >50% for the rate of patients achieving target serum urate (<6 mg/dl) was achieved (Table) for the overall population, independently of the aprioristic perception of the rate of target sUA or the presence of gold-standard diagnosis. A post-hoc analysis showed that in the subgroup of patients on urate-lowering medications, the improvement in the rate of patients achieving sA target was 49.31%, very close to the >50% improvement (Table). Both crystal based diagnosis and rate of sUa in target were higher in Units with dedicated crystal-arthritis office and also in those that had presented the EULAR 2006 recommendations at least once. Conclusions: Overall the improvement in the rate of patients achieving target serum urate over a 6-year period exceeded 50%. The rate of gold-standard diagnosis improved, but did not reach the expected outcome. Interest in recommendations and dedicated crystal arthritis offices were associated with best results. These preliminary data show for the first time that substantial improvement has been achieved in treat to target serum urate levels strategy for gout in the Rheumatology community. References: Perez-Ruiz F, et al. J Clin rheumatol 2011. Zhang W, et al. Ann Rheum Dis 2006. Acknowledgement: Funded by the Spanish Foundation for Rheumatology through an unrestricted grant from Menarini Spain Disclosure of Interest: None declared